Analisis Sektor Unggulan dalam Meningkatkan Perekonomian dan Pembangunan Wilayah Provinsi Jambi - Sudirman Sudirman; M Alhudhori (Universitas Batanghari, 2018)
Based on pattern classification Typologi Klassen of the growth sectors of the economy in Jambi province makes the agricultural sector and the sector of mining and excavation are on the I quadrant i.e. as a sector that developed and developing fast, water procurement sector, trash, waste treatment and recycling, and education services sectors are at a quadrant II sectors advanced but that is depressed. After dianalis the pattern of growth sectors of the economy, may be known to the classification of economic sectors in the province of Jambi, for a deeper analysis of the sector required base with LQ method to find the base of the sector can be prioritized into the flagship sector. In accordance with the results of the analysis of the economic base by the method of LQ for the level of Jambi province are known to exist in four major sectors constituting the base sector of the economy. The fourth sector is agriculture, a sector of mining and excavation of the procurement sector, garbage, water, sewage treatment and recycling, and educational services. So, from both Typologi and Klassen LQ analysis it can be concluded that the economic sector in Jambi province which should be developed and can be prioritized into a flagship sector is agriculture, a sector of mining and excavation, the sector procurement of waste, water, sewage treatment and recycling, and education services sectors. Keywords: (1) GDP Jambi province; Indonesia'S GDP and (2) the rate of growth of GDP and contribution to Indonesia and Jambi province; (3) Data on the economic potential of Jambi province